Chest Expansion and Lung Function for Healthy Subjects and Individuals With Pulmonary Disease. - Derasse, Marion; Lefebvre, Stéphanie; Liistro, Giuseppe; Reychler, Gregory (Respiratory Care, 2021)
BACKGROUND: The purposes of this study were to verify the correlation between chest expansion and lung function within a larger sample of subjects composed of both healthy subjects and subjects affected by pulmonary disease, and to verify the influence of age, body mass index, and gender on chest expansion. METHODS: Adults were recruited prospectively when they visited the lung function lab. Chest expansion was measured with a measuring tape at 2 different levels of the rib cage by 1 blinded examiner. Spirometry was performed for each subject. RESULTS: Data from 251 subjects between 18 and 88 y old were collected and analyzed. Among the analyzed subjects, mean upper and lower chest expansion were 4.82 6 1.84 cm and 3.99 6 2.15 cm, respectively. A significant but poor correlation was found between both chest expansion and all lung function parameters (total lung capacity, FVC, and FEV1)(P 5 .01). Negative significant correlations were found between chest expansion and age as well as body mass index. The difference in upper chest expansion between obese and nonobese subjects was not statistically significant, but the difference in lower chest expansion was significant for these 2 groups. Finally, upper and lower chest expansion were not different between males and females. CONCLUSIONS: Based on these results, one cannot validate the use of chest expansion measurement to define lung function. In centers that have easy access to more precise and complete methods to measure lung function, the measurement of chest expansion for diagnostic purposes seems to be archaic. Additionally, age and body mass index are 2 parameters that can influence chest expansion.